A methods engineering study on G & J Industrial Corporation - Carpio, Jenelyn Ann (College of Engineering, 2002)
A methods engineering study was conducted on G & J Industrial Corporation, a steel fabrication company manufacturing power transformer tanks and cabinets, with the intention of increasing the productivity and efficiency of the production processes through the application of techniques in IE 32. Data on the company's production system and operations gathered through interviews and observations; and subsequent analysis of such data using various analytical tools revealed that the main problem is the inability to meet the expected level of output in the production of power transformer tanks and cabinets. This problem is found to be caused by three inter-related areas of concern : a) unnecessary objects clutter the work area, b) there is a limited work area and c) there is no designated storage for raw materials and work in process components. The three principal causes of the main problem can be integrated into a single comprehensive problem, which is poor space management. Two alternatives were generated in order to address the problem. Both options present different plausible layouts relating to designation of particular work areas as well as materials storage. The total distance traveled by the material in each alternative was determined, and the alternative with the shortest distance was chosen. The chosen situation was Alternative 2, which features a central hub for the storage of raw materials and work in process components. An effective and detailed implementation plan was then devised in order execute the preferred solution.